Can illness beliefs, from the common-sense model, prospectively predict adherence to self-management behaviours?: a systematic review and meta-analysis - Aujla, Navneet; Walker, Marion; Sprigg, Nikola; Abrams, Keith; Massey, Adam; Vedhara, Kavita (Taylor and Francis, 2016)
Objective: To determine whether people’s beliefs about their illness, conceptualised by the common sense model (CSM), can prospectively predict adherence to self-management behaviours (including, attendance, medication, diet and exercise) in adults with acute and chronic physical illnesses.